From Lunar Modules to In-Situ Habs: Conceptualization & Considerations of a Developing Lunar South Pole Base - Dudzinski, Krystofer Leonard (2022)
This project delves into the strategic considerations of how a Lunar base may expand over time and theorizes how in-situ resource utilization (ISRU) technologies could be used to construct more robust and protective habitation that integrates with existing prefabricated modules for supporting large-scale surface operations. This ties into an exploratory conceptualization of how an example base at the Lunar south pole could take advantage of topography, local resources, and new construction technologies as it undergoes this infrastructural transition. Such pursuits are critical because future large-scale telerobotic ISRU activities (among many other upcoming Lunar operations) will require several month to year-long stays (or greater) of dozens of personnel in order to maximize crew effectiveness as they acquire invaluable on-site experience that is difficult to frequently replace. These increases in crew size and stay durations will require greater pressurized volumes within structures that are highly protective against radiation and micrometeorites while being maintainable for many years (ideally with local materials and producible parts). Prefabricated modules will eventually struggle to meet these requirements based on the mass and volume limitations of launch vehicles and the significant expenses involved in transporting material from Earth. In order to explore the architectural and technological steps needed to transition towards a large-scale Lunar facility, several research subtopics are included. This paper considered the structural, protective, and maintenance challenges in ISRU shell design and determined that 3D-printed sulfur concrete is the most promising shell material option currently. A trade study of various Lunar base typologies and the comparative factors that separate them is presented, which led to a crater facility being pursued for the in-situ habitat concept. Research is also laid out on the energy and operational needs of a base and the logistical and psychological needs of habitat ...